Compensatory post-diuretic renal sodium reabsorption is not a dominant mechanism of diuretic resistance in acute heart failure. (16th September 2021) - Cox, Zachary L; Rao, Veena S; Ivey-Miranda, Juan B; Moreno-Villagomez, Julieta; Mahoney, Devin; Ponikowski, Piotr; Biegus, Jan; Turner, Jeffrey M; Maulion, Christopher; Bellumkonda, Lavanya; Asher, Jennifer L; Parise, Helen; et al.
Abstract: Aims: In healthy volunteers, the kidney deploys compensatory post-diuretic sodium reabsorption (CPDSR) following loop diuretic-induced natriuresis, minimizing sodium excretion and producing a neutral sodium balance. CPDSR is extrapolated to non-euvolemic populations as a diuretic resistance mechanism; however, its importance in acute decompensated heart failure (ADHF) is unknown. Methods and results: Patients with ADHF in the Mechanisms of Diuretic Resistance cohort receiving intravenous loop diuretics (462 administrations in 285 patients) underwent supervised urine collections entailing an immediate pre-diuretic spot urine sample, then 6-h (diuretic-induced natriuresis period) and 18-h (post-diuretic period) urine collections. The average spot urine sodium concentration immediately prior to diuretic administration [median 15 h (13–17) after last diuretic] was 64 ± 33 mmol/L with only 4% of patients having low (<20 mmol/L) urine sodium consistent with CPDSR. Paradoxically, greater 6-h diuretic-induced natriuresis was associated with larger 18-h post-diuretic spontaneous natriuresis ( r  = 0.7, P  < 0.001). Higher pre-diuretic urine sodium to creatinine ratio ( r  = 0.37, P  < 0.001) was the strongest predictor of post-diuretic spontaneous natriuresis. In a subgroup of patients ( n  = 43) randomized to protocol-driven intensified diuretic therapies, the mean diuretic-induced natriuresis increased three-fold. In contrast to the substantial decrease in spontaneous natriuresis predicted by CPDSR, no change in post-diuretic spontaneous natriuresis was observed ( P  = 0.47). Conclusion: On a population level, CPDSR was not an important driver of diuretic resistance in hypervolemic ADHF. Contrary to CPDSR, a greater diuretic-induced natriuresis predicted a larger post-diuretic spontaneous natriuresis. Basal sodium avidity, rather than diuretic-induced CPDSR, appears to be the predominant determinate of both diuretic-induced and post-diuretic natriuresis in hypervolemic ADHF. Graphical Abstract: